HOMOLOGY MODELING AND DEVELOPMENT OF DIHYDRODIPICONILATE REDUCTASE INHIBITORS OF KLEBSIELLA PNEUMONIA: A COMPUTATIONAL APPROACH - Bhaskar, Baki Vijaya; Babu, Tirumalasetty Muni Chandra; Rajendra, Wudayagiri (International Journal of Current Pharmaceutical Research, 2016)
Objective: In order to development of novel, potent and selective inhibitors of Dihydropiconilate reductase (KpDHDPR) of multidrug resistant Klebsiella pneumonia. Methods: Protein sequence of KpDHDPR was retrieved from the UNIPROT and the primary and secondary structure was analyzed using Prot Param, SOPMA, GOR4 and Chou and Fasman. Afterword's, 3D structure of KpDHDPR was built by using MODELLEER9.14. The Molecular dynamics simulation was carried out using NAMD2.9 with CHARMM27 force field for 10 picoseconds and production run with for 400 picoseconds time period covered with water box. Molecular docking and virtual screening was carried out using Auto Dock Vina4.0 with PyRx interface. Bond angles, bond lengths, bond distances and binding interactions were analyzed using PyMol. Toxicity assessment and Lipinski rule of five of ligand were assessed using MOLINSPIRATION and OSIRIS Server. Results: 3D structure of KpDHDPR was resolved on the basis of EcDHDPR that revealed N-terminal nucleotide domain and C-terminal substrate binding domain which are connected by a short hinge region. Nucleotide binding domain is formed with seven Î±-helices and the Substrate binding domain is composed with three Î±-helices and Rossman fold is observed with four Î±-helices and seven Î²-strands. Molecular docking analysis revealed that NADPH has exhibited more binding affinity to KpDHDPR than NADH. As results of virtual screening and docking, six compounds viz. ZINC04280533, ZINC04280532, ZINC04280468, ZINC33378709, ZINC05280538 and ZINC25694354 were identified. Bioavailability of these inhibitors are comply with the Lipinski rule of five, good pharmacokinetic and drug likeness properties. Conclusion: In conclusion, in silico studies revealed that these lead scaffolds could helpful in the development of KpDHDP R inhibitors. Hence, these drug candidates might be promoted as promising antibacterial agents for the treatment of drug resistant gram negative bacterial infections.